Vulnerability in the Information Age - What Browsers Reveal - Albuquerque, Brunna; Regis, Carlos Filipe; Moreira, Josilene Aires (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
The exponential growth in the use of web services and applications has increased the amount of personal information registered on websites and databases worldwide. Consequently, users are more exposed to vulnerability flaws and more subject to the impact of leaking this information. This article investigates how personal information is handled by three popular browsers: Internet Explorer, Mozilla Firefox and Google Chrome, by analyzing data collected in shared research laboratories. Through the analysis of data stored by browsers on a shared computer laboratory, we found a large number of cookies with important personal information, showing that these browsers can reveal more than the users would like.